Dysglycaemias among Patients with Chronic Kidney Disease in Tanzania (Tanzania Medical Journal, 2022)
BackgroundChronic Kidney Disease (CKD) contributes to significant morbidity and mortality around the globe and especially so in the sub-Saharan Africa region. CKD influences the control of blood glucose levels resulting in glycemic dysregulation (causing either hypoglycemia or hyperglycemia) through various proposed pathways. In this study we investigated on prevalence, patterns and factors associated with dysglycaemias among patients with CKD attended at the tertiary Muhimbili National Hospital, Dar es Salaam, Tanzania.Materials and MethodsWe carried out a hospital based cross-sectional study between July 2017 and January 2018. Employing a systematic sampling method, we enrolled a total of 328 patients with CKD who were attended at the Renal Unit of the Muhimbili National Hospital in Dar es Salaam, Tanzania. We performed Oral Glucose Tolerance Test (OGTT) to selected patients and recorded their respective glycemic levels. We used SPSS version 20.0 for data analysis.ResultsOf the 328 selected patients; 128 (39%) were patients with known (established) diabetes mellitus, 7 (2.1%) were (newly) diagnosed to have diabetes mellitus and 17 (5.2%) were found to have impaired glucose tolerance by OGTT during this study. Furthermore, of the 128 patients with established diabetes mellitus; 7(5.5%) were found to have hypoglycemia and 20 (15.6%) had developed “burnt-out” diabetes mellitus, respectively. On multivariate analysis; age 50 years or more (OR 2.92, 95% C.I. (1.71 - 4.99)), having co-existent hypertension (OR 2.96 (1.71 - 4.99)) and having a positive family history of diabetes mellitus (OR 7.8 (3.74 – 17.02)) were found to be independent factors associated with presence of dysglycaemias.ConclusionDiabetes mellitus, impaired glucose tolerance, hypoglycemia and “burnt out” diabetes mellitus are all prevalent among patients with CKD attended at the Renal Unit of Muhimbili National Hospital, Dar es Salaam, Tanzania.  Having age 50 years or older, family history of diabetes and co-existent hypertension are independent predictors of dysglycaemias among these patients.